2019
DOI: 10.21522/tijph.2013.07.03.art018
|View full text |Cite
|
Sign up to set email alerts
|

The Proportion and Nature of Disrespect and Abuse during facility-based care in a rural and an urban setting in Kano, northwest Nigeria; A mixed-method study

Abstract: Objectives: Disrespect and abuse is noted to be high but poorly reported, especially in northern Nigeria. This study was undertaken to determine the proportion and nature of disrespect and abuse of women during childbirths in health facilities at selected locations in Kano, a northwest Nigerian State Method: Ethical approval and informed consent were obtained. The study adopted quantitative and qualitative data collection methods. A sample size of 292 women who delivered in the past 1year preceding the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
1
Order By: Relevance
“…In this study, 56.3% of women received respectful care (95% CI: 52.0, 61.4%) which is similar to that of a study conducted in public health facilities of Bahir Dar town which showed the status of compassionate and respectful care was 57% 11 and Kano, Nigeria (56.48%). 13 The finding of this study is lower than that of a study conducted in the Bale zone which stated that the status of respectful maternity care was 62.5% 9 and Kenya (80%). 6 This might be due to the study conducted in Kenya assessed disrespectful and abusive care after the implementation of a package of interventions and staff training.…”
Section: Discussioncontrasting
confidence: 78%
“…In this study, 56.3% of women received respectful care (95% CI: 52.0, 61.4%) which is similar to that of a study conducted in public health facilities of Bahir Dar town which showed the status of compassionate and respectful care was 57% 11 and Kano, Nigeria (56.48%). 13 The finding of this study is lower than that of a study conducted in the Bale zone which stated that the status of respectful maternity care was 62.5% 9 and Kenya (80%). 6 This might be due to the study conducted in Kenya assessed disrespectful and abusive care after the implementation of a package of interventions and staff training.…”
Section: Discussioncontrasting
confidence: 78%